Implementation of SISKEUDES Online and CMS in Mar-tadana Village Financial Management (International Journal of Social Welfare and Family Law, 2026)
This study aims to analyze the implementation of the Online Village Financial System Application (SISKEUDES) and Cash Management System (CMS) in village financial management and to identify the impacts of their implementation. This study employs a descriptive qualitative research design. Data were collected through interviews, observation, and documentation. The data analysis technique uses the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The informants in this study consisted of six people, namely the Head of Government Section of Pengkadan District, the Head of Martadana Village, the Village Secretary, the Head of Financial Affairs as the SISKEUDES Online operator, the Head of Government Section of Martadana Village as the budget activity implementer for village governance administration and community development, and the Head of Welfare and Services Section as the budget activity implementer for village development, community empowerment, and village emergency and urgent affairs. The findings indicate that the implementation of the SISKEUDES Online application in Martadana Village has been running well, although it is sometimes constrained by poor signal quality. This is evidenced by increasingly transparent and accountable village financial management, as well as by village officials who are greatly assisted in preparing financial reports. The use of Bank Kalbar's Cash Management System (CMS) has also been running well, as shown by the increasing efficiency and effectiveness of the village government in conducting financial transactions.